2017
DOI: 10.1111/1471-0528.14593
|View full text |Cite
|
Sign up to set email alerts
|

The impact of subcutaneous tissue suturing at caesarean section on wound complications: a meta‐analysis

Abstract: databases together with reference lists from included studies.Selection criteria Randomised and quasi-randomised trials that investigated the impact of subcutaneous tissue suturing on wound complications following caesarean section were held eligible for inclusion. Retrospective studies and prospective nonrandomised studies were excluded from the present meta-analysis.Data collection and analysis The methodological quality of studies was assessed with the Jadad scale. Statistical meta-analysis was performed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…An updated meta-analysis by Pergialiotis et al confirmed these findings with more than double the number of patients. The likelihood of developing a wound infection was not significantly different between the closure group and the nonclosure group (OR 0.99, 95% CI 0.70 to 1.41) (Pergialiotis et al 2017).…”
Section: Wound Closurementioning
confidence: 79%
“…An updated meta-analysis by Pergialiotis et al confirmed these findings with more than double the number of patients. The likelihood of developing a wound infection was not significantly different between the closure group and the nonclosure group (OR 0.99, 95% CI 0.70 to 1.41) (Pergialiotis et al 2017).…”
Section: Wound Closurementioning
confidence: 79%
“…Higher dose antibiotics may be beneficial 43 . To reduce the risk of wound complications, women with more than 2 cm subcutaneous fat should have suturing of the subcutaneous tissue following cesarean delivery 37,86,103,139 . Subcutaneous drains can increase risk of wound complications and are therefore not recommended for routine use 44 .…”
Section: Figo Guidance For Pregnancy Obesitymentioning
confidence: 99%
“… 4 Two additional RCTs and a meta-analysis since supports re-approximating this tissue layer as previously recommended. 75 77 …”
Section: Standardized Cesarean Delivery Surgical Techniquementioning
confidence: 99%